2020
DOI: 10.3389/fneur.2020.587226
|View full text |Cite
|
Sign up to set email alerts
|

Encephalopathy in COVID-19 Presenting With Acute Aphasia Mimicking Stroke

Abstract: Introduction: Neurological manifestations are emerging as relatively frequent complications of corona virus disease 2019 (COVID-19), including stroke and encephalopathy. Clinical characteristics of the latter are heterogeneous and not yet fully elucidated, while the pathogenesis appears related to neuroinflammation in a subset of patients. Case: A middle-aged man presented with acute language disturbance at the emergency department. Examination revealed expressive aphasia, mild ideomotor slowing, and severe hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…As is evident by the fact that 303/430 (70%) patients we identified had CSF SARS-CoV-2 PCR testing performed, it is feasible to perform PCR testing for SARS-CoV-2 in CSF [5-10,15,17,22,24,26-38,43-59, 68-71,73,74,76-78,81,84,88,89,95,97,98,101,103,105,108,109,111, 113,116 156,157,161,164,165,169,171,177,178,[180][181][182][184][185][186][187]190,191,193,[195][196][197][198][199][200][201][203][204][205][206][207]209,[212][213][214][215][216][218][219][220][221][224][225][226][227]230,[233]…”
Section: Discussionmentioning
confidence: 99%
“…As is evident by the fact that 303/430 (70%) patients we identified had CSF SARS-CoV-2 PCR testing performed, it is feasible to perform PCR testing for SARS-CoV-2 in CSF [5-10,15,17,22,24,26-38,43-59, 68-71,73,74,76-78,81,84,88,89,95,97,98,101,103,105,108,109,111, 113,116 156,157,161,164,165,169,171,177,178,[180][181][182][184][185][186][187]190,191,193,[195][196][197][198][199][200][201][203][204][205][206][207]209,[212][213][214][215][216][218][219][220][221][224][225][226][227]230,[233]…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, CSF analysis showed the presence of blood-brain barrier (BBB) dysfunction and a CSF increase in IL-6–IL-8 levels, in parallel with cytokine level increase in serum [ 54 , 62 ]. Patients receiving immunotherapy, intravenous immunoglobulins and/or steroids, plasmapheresis, and tocilizumab [ 54 56 , 59 , 61 , 68 , 69 ] improved, but spontaneous recovery cannot be excluded, since COVID-19-related encephalopathy may have a self-limited course even without a specific therapy [ 15 , 37 , 70 ]. Unfortunately, very few studies assessed cytokine levels in both serum and CSF, in order to correlate disease course with cytokine levels following treatment.…”
Section: Pros: Cognitive and Behavioral Manifestations Of Covid-19 Armentioning
confidence: 99%
“…Of 242 publications from December 1, 2019 and November 18, 2020 that described a unique patient diagnosed with COVID-19 via SARS-CoV-2 PCR or serology who had a neurological symptom and had CSF obtained, we identified 51 that met inclusion criteria. After review of the 51 publications, we identified 70 patients reported to have altered olfactory and/or gustatory function (anosmia/cacosmia/hyposmia and/or ageusia/dysgeusia/hypogeusia); 40 (57%) had both olfactory and gustatory dysfunction, 17 (24%) had isolated olfactory dysfunction and 13 (19%) had isolated gustatory dysfunction [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] . In addition to altered olfactory and/or gustatory function, 39 (56%) had symptoms that localized to the central nervous system and 31 (44%) had symptoms that localized to the peripheral nervous system.…”
Section: Resultsmentioning
confidence: 99%
“…In 13/66 (20%) patients, the CSF WBC count was 0 cells/µL or the CSF WBC:RBC ratio was <1:1,000. The majority of patients (38/66; 58%) had a CSF WBC count of 1-5 cells/µL or were noted to have “no pleocytosis” or “normal WBC.” [10] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [29] , [30] , [33] , [36] , [37] , [38] , [40] , [41] , [42] , [44] , [45] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] There were 11/66 (17%) patients who had a CSF WBC count >5 cells/µL or noted to be “increased.” [8] , [12] , [17] , [28] , [31] , [32] , [33] , [34] , [35] , [39] , [46]
Fig. 3 Cerebrospinal Fluid White Blood Cell Count Results.
…”
Section: Resultsmentioning
confidence: 99%